Association of Biochemically Verified Post-Diagnosis Smoking and Nonmuscle-Invasive Bladder Cancer Recurrence Risk. Issue 6 (27th June 2022) - Furberg, Helena; Petruzella, Stacey; Whiting, Karissa; Stein, Emily; Orlow, Irene; Kenney, Jessica; Corrales-Guerrero, Sergio; Benfante, Nicole; Cha, Eugene K.; Donahue, Timothy F.; Donat, Sherri M.; Herr, Harry W.; et al.
Abstract : Purpose: Our goal was to determine the association between biochemically verified post-diagnosis smoking exposure and nonmuscle-invasive bladder cancer (NMIBC) recurrence risk. Materials and Methods: We conducted a prospective study of 354 NMIBC patients with a smoking history undergoing care between 2015 and 2018. Patients contributed at least 2 biospecimens during followup which were tested for cotinine to determine biochemically verified post-diagnosis smoking exposure (yes/no). Our primary endpoint was time to first recurrence after study start date. We examined whether post-diagnosis smoking exposure was associated with recurrence risk in multivariable Cox proportional hazards models that accounted for demographics, clinicopathological variables, time since diagnosis and pack-years. Results: Patients were predominantly White, male and had a median age of 68 years. Most patients had Ta disease (62%) and tumors of high grade (68%). Intravesical bacillus Calmette-Guérin was given to 63% of the cohort. Patients were followed for a median of 3.6 years since study start. Post-diagnosis smoking exposure was detected in 22% of patients, and 38.7% (137) of patients experienced a recurrence during followup. In multivariable models, only bacillus Calmette-Guérin treatment and prior recurrence rate were significantly associated with recurrence. There was no association between post-diagnosis smoking exposure and recurrence risk (HR: 0.73, 95% CI: 0.45–1.20). Conclusions: In a cohort of patients with predominantly high risk NMIBC, post-diagnosis smoking exposure was not associated with NMIBC recurrence. However, smoking cessation support remains a critical component of cancer care given that the benefits of quitting extend far beyond NMIBC recurrence.